9‐5L: Late‐News Paper: 6Gb/s Ultra Definition Display Interface (UDDI) for Large‐size 8K Displays. Issue 1 (2nd June 2017) - Amirkhany, Amir; Hekmat, Mohammad; Sankaranarayanan, Sabarish; Jose, Anup; Abramzon, Valentin; Jaffari, Nancy; Saito, Keisuke; Elzeftawi, Mohamed; Wang, Michael; Moballegh, Shiva; Malhotra, Gaurav; Kamali, Jalil; et al.
Abstract : A 6Gb/s per lane ultra‐definition display interface (UDDI) system is presented to reduce the production cost and to improve the form‐factor of Quad‐UHD TV panels. The receiver (RX) is implemented in a 0.18um Source IC process. The transmitter (TX) is fabricated in a low‐leakage 65nm process for integration with a Timing Controller (TCON) ASIC. The analog front‐end of the receiver is equipped with a continuous‐time linear equalizer and a 5‐tap decision feedback equalizer. Continuous calibration and adaptation engines in the receiver ensure reliable communication over an extended operation period. The transmitter employs 3‐tap pre‐emphasis for channel equalization and a dual‐VCO LC PLL for low jitter transmission. System link layer employs a low‐overhead error correction code to protect video data against random errors and to limit worst‐case run‐length. The system also deploys scrambling to reduce EMI. Noise‐free video quality was achieved at 6Gb/s over 65" display Source PCBs and at 4Gb/s over 105" display Source PCBs. The UDDI system improves the highest existing intra‐panel interface speed by nearly a factor of 2.